Community engagement is … : revisiting Boyer's model of scholarship. Issue 6 (18th September 2020) - Renwick, Kerry; Selkrig, Mark; Manathunga, Catherine; Keamy, Ron 'Kim'
ABSTRACT: Criticisms have been levelled at academics at a time when funding of universities is increasingly tied to private and corporate purposes and when academics are held accountable through a hierarchy of functions. Claims are also made that academics work within narrow specializations and are removed from real-world experience and problems. Boyer's model of scholarship offers four categories of scholarship that remain relevant to understanding and guiding the work of academics, including how they engage with communities. To explore the nature of academics' work, we draw on data provided by a group of academics who participated in a research project using both sociological elicitation and visual arts-based research methodologies. The participants were asked to explore what various aspects of current academic work mean for them by providing an image and text, akin to creating a postcard. In this article, we focus on responses they provided to the prompt 'Community engagement is … ' The postcards show how community engagement can be interpreted in diverse ways and that, along with teaching and research, community engagement are all integrated, mutually reinforcing drivers and outcomes of academic work.